2007
DOI: 10.1007/s11069-007-9124-3
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integrated management framework for emerging disaster risks in Japan

Abstract: An integrated framework for disaster risk management is presented to cope with the risk of low-probability high-consequence (LPHC) disasters in urban communities. Since the 2000 Tokai flood in Japan, there has been a shift in the management strategy from disaster prevention with a presumed zero risk to disaster reduction with an acceptable risk. The framework consists of: (i) integration of a different categories of risk reduction options in terms of structural and nonstructural measures, regulation and market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 6 publications
0
36
0
2
Order By: Relevance
“…These functions of WebGIS can be applied to understand risks to allow communities to better prepare and respond to them [122,123]. Workshops of scenario-based risk communication with the local community are effective for enhancing the local capacity for handling DRM information platforms [124].…”
Section: Webgismentioning
confidence: 99%
“…These functions of WebGIS can be applied to understand risks to allow communities to better prepare and respond to them [122,123]. Workshops of scenario-based risk communication with the local community are effective for enhancing the local capacity for handling DRM information platforms [124].…”
Section: Webgismentioning
confidence: 99%
“…As far as research on disaster risk management in Japan is concerned, DPRI (Disaster Prevention Research Institute, Kyoto University) and IIASA (International Institute for Applied Systems Analysis) initiated jointly the Integrated Disaster Risk Management Project in 2001 (Amendola et al 2008). In the same year, NIED also began a project Social Systems Resilient to Disasters to explore various integrative approaches to risk management based on case studies in local communities in order to reorganize coping capability against disaster risk in Japan (Ikeda, Sato, and Fukuzono 2008). Various types of integrated management approaches and tools of communicating risks among stakeholders were developed to support the improvement of the residents' understanding of risk information about such issues as the nature of disaster risk, the content of hazard maps, types of disaster insurance, measures and routes of evacuation, and other countermeasures to respond in advance to risks (Ammann 2006;Alexander 2006;).…”
Section: From Traditional Risk Management To Risk Governancementioning
confidence: 99%
“…In the United Kingdom, the Flood Foresight project concluded that expected annual flood damages may increase twentyfold by the 2080s if flood risk management policy were to remain as it is at present (Evans et al 2004;Hall, Sayers, and Dawson 2005). In Japan, Ikeda, Sato, and Fukuzono (2008) developed various flood risk scenarios in their search for resilient social systems against flood disasters.…”
Section: Pathways For the Future-scenariosmentioning
confidence: 99%